Streptomyces dangxiongensis sp. nov., isolated from soil of Qinghai-Tibet Plateau. Issue 9 (24th June 2019) - Zhang, Binglin; Tang, Shukun; Yang, Ruiqi; Chen, Ximing; Zhang, Dongming; Zhang, Wei; Li, Shiweng; Chen, Tuo; Liu, Guangxiu; Dyson, Paul
Abstract : A novel actinobacterial strain, designated Z022 T, isolated from a soil sample collected from Dangxiong in Tibet Autonomous Region (PR China), was determined by polyphasic taxonomic approach. The organism had chemotaxonomic and morphological properties consistent with its classification in the genus Streptomyces . Strain Z022 T showed high similarity value to Streptomyces lucensis NBRC 13056 T (98.87 %) and S. achromogenes subsp . achromogenes NBRC 12735 T (98.68 %) based on the 16S rRNA gene phylogenetic tree. The genomic DNA G+C content of strain Z022 T based on the genome sequence was 72.16 mol%. DNA–DNA relatedness values between strain Z022 T and strain Streptomyces lucensis NBRC 13056 T was 23.7±1.3 % and signiﬁcantly lower than 70 %. Chemotaxonomic data revealed that strain Z022 T possessed MK-9(H8 ) and MK-9(H6 ) as the predominant menaquinone, ll -diaminopimelic acid as the diagnostic diamino acid, and galactose, glucose, xylose and ribose as whole cell sugars. Diphosphatidylglycerol (DPG) and phosphatidylethanolamine (PE) were the predominant polar lipids; anteiso-C15 : 0, iso-C16 : 0, and anteiso-C17 : 0 were the major fatty acids. On the basis of these genotypic and phenotypic data, it is proposed that isolate Z022 T (=JCM 31053 T =CGMCC 4.7273 T ) should be classified in the genus Streptomyces as Streptomyces dangxiongensis sp. nov.